IL-12p40 deletion aggravates lipopolysaccharide-induced cardiac dysfunction in mice - Liu, Menglin; Wang, Zhen; Zhang, Jishou; Ye, Di; Wang, Menglong; Xu, Yao; Zhao, Mengmeng; Feng, Yongqi; Lu, Xiyi; Pan, Heng; Pan, Wei; Wei, Cheng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac dysfunction is one of the most common complications of sepsis and is associated with the adverse outcomes and high mortality of sepsis patients. IL-12p40, the common subunit of IL-12 and IL-23, has been shown to be involved in a variety of inflammation-related diseases, such as psoriasis and inflammatory bowel disease. However, the role of IL-12p40 in lipopolysaccharide (LPS)-induced cardiac dysfunction remains obscure. This study aimed to explore the role of IL-12p40 in LPS-induced cardiac dysfunction and its potential mechanisms. Methods In this study, mice were treated with LPS and the cardiac expression of IL-12p40 was determined. Then, IL-12p40-/- mice were used to detect the role and mechanisms of IL-12p40 in LPS-induced cardiac injury. In addition, monocytes were adoptively transferred to IL-12p40-/- mice to explore their effects on LPS-induced cardiac dysfunction. Results The results showed that cardiac IL-12p40 expression was significantly increased after treatment with LPS. In addition, IL-12p40 deletion significantly aggravated LPS-induced cardiac dysfunction, as evidenced by the increased serum levels of cardiomyocyte injury markers and deteriorated cardiac function. Moreover, IL-12p40 deletion enhanced LPS-induced monocyte accumulation and cardiac expression of inflammatory cytokines and increased the phosphorylation levels of p65 (p-p65). Furthermore, adoptive transfer WT mouse monocytes to IL-12p40-/- mice alleviated LPS-induced cardiac dysfunction. Conclusion IL-12p40 deletion significantly aggravated LPS-induced cardiac injury and cardiac dysfunction in mice by regulating the NF-κB signalling pathway, and this process was related to monocytes. Therefore, IL-12p40 may be an attractive target for sepsis-induced cardiac dysfunction.